2001
DOI: 10.1016/s0301-0546(01)79046-5
|View full text |Cite
|
Sign up to set email alerts
|

Piroxicam-induced photodermatitis. Cross-reactivity among oxicams. A case report

Abstract: we present a case of photodermatitis and dermatitis to piroxicam, in a patient with contact allergy to the thiosalicylic moiety of thimerosal, in which cross-reactivity with the other oxicams have been demonstrated. In cases of oxicams-induced photodermatitis, all oxicams should be avoided, to elude posible cross-reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…But there was no cross-reaction with tenoxicam and lenoxicam and only 1/31 had positive photopatch tests with meloxicam. In contrast, in 1 case with a photosensitization to piroxicam, all photopatch tests done with piroxicam, tenoxicam, droxicam and meloxicam were positive [122] . However, in 8 patients with FDE, cross-reactions between oxicams were very frequent [123] .…”
Section: Usefulness Of Drug Skin Tests To Study Cross-reactivity Betwmentioning
confidence: 80%
“…But there was no cross-reaction with tenoxicam and lenoxicam and only 1/31 had positive photopatch tests with meloxicam. In contrast, in 1 case with a photosensitization to piroxicam, all photopatch tests done with piroxicam, tenoxicam, droxicam and meloxicam were positive [122] . However, in 8 patients with FDE, cross-reactions between oxicams were very frequent [123] .…”
Section: Usefulness Of Drug Skin Tests To Study Cross-reactivity Betwmentioning
confidence: 80%
“…Some reports have described dyshidrosiform dermatitis associated with photoallergic eruption in patients who had received oral piroxicam, but no one previously has reported dyshidrosiform dermatitis alone (3–6).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms are not fully explained, but it is suggested that the NSAIDs could act as a hapten, binding to a protein bound to melanocytes, and producing a specific cytotoxic reaction directed at the melanocytes bound by the hapten. The drugs most frequently associated with this adverse reaction are paracetamol, salicylates, derivatives of oxicam, and ibuprofen [42][43][44][45] (Figure 4).…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%